Investigating the Performance of Selective Attention and Working Memory in Adolescents Recovered from Acute Covid-19 with Normal Adolescents - Asadi Rajani, Maede (International Journal of Education and Cognitive Sciences, 2022)
Selective attention is a state of attention in which a person can choose the target stimulus from among various stimuli and track it. A body of research shows that covid-19 infection is associated with cognitive deficits. Therefore, the aim of the present study is to investigate the performance of selective attention and working memory in adolescents recovered from acute and normal covid-19. The current study was a causal-comparative which was conducted on 59 adolescents aged 15 to 20 years who recovered from acute and normal covid-19 in 1400 in Karaj city, Iran. Selective attention was evaluated through the complex Stroop word software test and active memory through the Wechsler memory test, and Goldberg mental health questionnaire and the Wechsler intelligence test for blind people. By comparing the average scores of the two groups, it can be seen that the selective attention of normal adolescents is higher compared to adolescents who have recovered from acute Covid-19. By comparing the average scores of the two groups, it can be seen that the working memory of normal adolescents is higher compared to adolescents who have recovered from acute Covid-19. Based on the findings of the present study, selective attention and active memory of the recovered adolescent have been affected by Covid-19 during this period. Based on this, it is suggested to conduct research with a wider statistical population to identify the types of cognitive weaknesses of people who have recovered from Covid-19, so that major cognitive disorders can be prevented in time.